2020
DOI: 10.1103/physrevlett.124.027205
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Scaling of Charge and Spin Responses at a Kondo Destruction Quantum Critical Point

Abstract: Quantum critical points often arise in metals perched at the border of an antiferromagnetic order. The recent observation of singular and dynamically scaling charge conductivity in an antiferromagnetic quantum critical heavy fermion metal implicates beyond-Landau quantum criticality. Here we study the charge and spin dynamics of a Kondo destruction quantum critical point (QCP), as realized in an SU(2)-symmetric Bose-Fermi Kondo model. We find that the critical exponents and scaling functions of the spin and si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Because the magnetic quantum phase transition is accompanied by the transition from a phase with asymptotically decoupled local-moment and conductionelectron degrees of freedom to one in which the entangling of the two turns the 4f local moments into composite quasiparticles, it is natural that both the single-particle and charge dynamics are critical. Indeed, calculations at the Kondo-destruction QCP in various large-N limits (Cai et al, 2020;Kirchner et al, 2005;Komijani and Coleman, 2019;Zhu et al, 2004) and, more recently, in the physical N = 2 case (Cai et al, 2020) have shown such a singular charge dynamics. Intriguingly, this type of charge dynamical scaling in models of the Kondo limit smoothly connects to the ω/T -scaling for the charge dynamics in the beyond-Landau-type quantum criticality in the mixed-valence regime (Pixley et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Because the magnetic quantum phase transition is accompanied by the transition from a phase with asymptotically decoupled local-moment and conductionelectron degrees of freedom to one in which the entangling of the two turns the 4f local moments into composite quasiparticles, it is natural that both the single-particle and charge dynamics are critical. Indeed, calculations at the Kondo-destruction QCP in various large-N limits (Cai et al, 2020;Kirchner et al, 2005;Komijani and Coleman, 2019;Zhu et al, 2004) and, more recently, in the physical N = 2 case (Cai et al, 2020) have shown such a singular charge dynamics. Intriguingly, this type of charge dynamical scaling in models of the Kondo limit smoothly connects to the ω/T -scaling for the charge dynamics in the beyond-Landau-type quantum criticality in the mixed-valence regime (Pixley et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…The self-consistency on spin correlators has only been systematically justified in models with random exchange, like those considered above, as we noted at the end of Section VII.A. The numerical analyses were carried out for Ising spin symmetry (Glossop and Ingersent, 2007;Grempel and Si, 2003;Zhu et al, 2003Zhu et al, , 2007, although recent works have also examined SU(2) spin symmetry (Cai et al, 2020;Hu et al, 2020). Aspects of these studies are similar to the RG results described in Section VIII.D, with a SYK-like spin spectral density (i.e.…”
Section: E Numerical Analysismentioning
confidence: 99%
“…The dynamical large-N method is not capable of capturing the local Fermi liquid fixed point and instead results in an intermediate coupling fixed point that corresponds to an overscreened multichannel Kondo ground state possessing non-Fermi liquid properties [50,51]. This short-coming not withstanding, the large-N method yields controlled results for the critical properties of the pseudogap Kondo model and sub-Ohmic BFKM that are in line with those obtained using NRG and CT-QMC [24,38,52].…”
Section: Models Of Critical Kondo Destructionmentioning
confidence: 68%
“…As non-trivial ω/T scaling is not expected within the standard Landau-Ginzburg framework for magnetic criticality [1,36], it can serve as a diagnostic tool for unconventional criticality. It has been demonstrated that the spin-isotropic BFKM displays ω/T scaling at its Kondo-destroying QCP [37,38]. In the BFKM, Kondo screening becomes critical due to the competition with a singular bosonic bath.…”
Section: Models Of Critical Kondo Destructionmentioning
confidence: 99%
See 1 more Smart Citation